1996
DOI: 10.1002/chin.199633261
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Electrodeposition of In‐Se, Cu‐Se, and Cu‐In‐Se Thin Films.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…InSe thin films were deposited from acidic aqueous solutions containing In 3+ and SeO 2 (or H 2 SeO 3 ) at potentials that ranged from −0.8 to −1.35 V vs. SCE [49][50][51][52][53][54][55] . The indium ions were from chloride 49,50,54,55) or sulfate [51][52][53] salts.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…InSe thin films were deposited from acidic aqueous solutions containing In 3+ and SeO 2 (or H 2 SeO 3 ) at potentials that ranged from −0.8 to −1.35 V vs. SCE [49][50][51][52][53][54][55] . The indium ions were from chloride 49,50,54,55) or sulfate [51][52][53] salts.…”
Section: )mentioning
confidence: 99%
“…The indium ions were from chloride 49,50,54,55) or sulfate [51][52][53] salts. In the deposition of InSe, the pH of the bath solution was below 1. , and citrate, with a pH of 2 at a potential of −1.6 V vs. MSE for 45 min.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The deposits may contain the species in elemental form, but more likely in the form of binary or ternary compounds depending on the number of species in solution. The applied potential does not need to be constant: it has been shown that use of a voltage ramp can assist the incorporation of electronegative elements and reduce dendritic growth [28] . Whatever the potential program used, the question arises -which compounds will be formed?…”
Section: Electrodepositionmentioning
confidence: 99%
“…As far as we are aware, this approach has only been used for CuInSe 2 [28,41,42] , although there is no reason to suppose that it would not work for other systems. The deposition of both Cu -Se and In -Se compounds is mass transport limited, and the process is complicated by the fact that several phases with different stoichiometries can be formed within a narrow range of experimental conditions (see Section 1.2.3.2.2 ).…”
Section: Summary Of Eda Routesmentioning
confidence: 99%